Microparticles containing moxidectin and sustained release injectable composition containing the same
By microparticulate moxifloxacin preparations and using biodegradable polymers to make microparticles, the existing canine heart tapeworm prevention drugs have short half-life and regular administrators have been solved, and the continuous release of moxifloxacin and the prolonged prevention effect has been achieved.
Patent Information
- Application Number
- JP2024560399
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-13
- Filing Date
- 2022-04-27
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-04-27
AI Technical Summary
The existing canine heart tapeworm prevention drugs have a short half-life and require regular monthly administer, which leads to inconvenient use and easy to forget, increasing the risk of infection.
The microparticulated moxidectin preparation was developed, and particles were made from biodegradable polymers, with an average diameter of 60-110 μm. Moxidectin was gradually released through the biodegradation of the particles, and the effective blood drug concentration was maintained for more than three months.
The continuous release of moxifloxacin was achieved for more than three months, extending the effect of preventing canine heart tapeworms and reducing the foreign body sensing and pain caused by injection.
Smart Images

Figure 2025513848000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to microparticles containing moxidectin and sustained-release injectable compositions containing the same. [Background technology]
[0002] Heartworm Disease (HWD) is a mosquito-transmitted parasite called Dirofilaria immitis that infects dogs, cats, and ferrets. As the name suggests, HWD resides in the heart of mammals.
[0003] Adult heartworms grow up to 30cm and mainly infest the pulmonary artery and right ventricle. Mature female and male heartworms produce very small larvae called microfilariae (L1). These larvae infest the blood of infected animals and infect other animals through mosquitoes. After two weeks, L1 larvae become infective and can be transmitted to other animals through mosquitoes. Larvae that infect other animals undergo several stages of growth and migrate to the pulmonary artery after 3 to 4 months. Mature adult heartworms live for an average of 5 to 7 years, and female and male heartworms produce many larvae through reproduction.
[0004] An infected animal's heart and pulmonary arteries can contain as few as one heartworm or as many as 200. Infection causes the pulmonary arteries to thicken and become inflamed, forcing the heart to work harder to move blood around the heartworms and into the lungs. The lungs also become inflamed. When the number of heartworms is low, there may be no particular symptoms, but animals infected with heartworms generally show early symptoms such as avoidance of exercise, coughing, and weight loss. In severe infections, symptoms such as severe coughing, difficulty breathing, and heart failure may appear. When an animal infected with heartworms shows these symptoms, it can even die from heart failure.
[0005] If a diagnosis of heartworm infection is confirmed, treatment can be carried out with caparsolate to kill the adult heartworms or with melarsomine, both of which have side effects such as severe irritation at the injection site and some damage to the liver and kidneys.
[0006] For this reason, it is economical and safe to prevent heartworm infection before it occurs. Prevention should be done when the dog is 6-8 weeks old. Heartworm preventatives include diethylcarbamazine (DEC) given daily, or ivermectin, milbemycin, moxidectin, and selamectin given monthly. All preventatives are highly effective when administered correctly, but because they must be given daily or monthly, even forgetting to give them a few times puts the dog at risk of infection.
[0007] For this reason, there is an urgent need to develop a heartworm preventative that uses moxidectin, which can prevent heartworms, and maintains its efficacy for more than three months with a single dose, thereby improving the convenience of administration. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 10-2006-0005472 Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide microparticles containing moxidectin and sustained-release injectable compositions containing the same.
[0010] Another object of the present invention is to provide microparticles containing moxidectin which, unlike conventional heartworm preventive drugs that have a short half-life and must be administered regularly every month, can maintain their heartworm preventive effect by continuously releasing moxidectin for three months or more when administered.
[0011] Another object of the present invention is to provide a sustained release injectable composition containing moxidectin, which can prevent initial excessive release of moxidectin and control the release of the drug, thereby maintaining a constant effective concentration of moxidectin for three months or more, even when the microparticles are administered, and can reduce foreign body sensation and pain when the injection is administered. [Means for solving the problem]
[0012] In order to achieve the above-mentioned object, the microparticles containing moxidectin of the present invention are microparticles containing moxidectin and a biodegradable polymer, and the intrinsic viscosity of the biodegradable polymer may be 0.1 dl / g to 1 dl / g, and the average diameter of the microparticles may be 60 to 110 μm.
[0013] The microparticles may be spherical and contain moxidectin uniformly within the microparticles.
[0014] The coefficient of variation (CV) of the microparticles may be 5% to 20%.
[0015] The microparticles may contain a biodegradable polymer and moxidectin in a weight ratio of 2:1 to 12:1.
[0016] The microparticles are capable of sustained release of moxidectin for more than three months.
[0017] The biodegradable polymer may be selected from the group consisting of polylactide (PLA), polylactide-co-glycolide (PLGA), polyphosphazenes, polyiminocarbonates, polyphosphoesters, polyanhydrides, polyorthoesters, polycaprolactones, polyhydroxyvalers, polyhydroxybutyrates, polyamino acids, and mixtures thereof.
[0018] The microparticles may have a molecular weight of 0.3 to 3 according to the following formula 1. [Formula 1] C max-peak n / C max―peak n+1
[0019] Where: Microparticles containing moxidectin were mixed with a suspension solution to prepare an injection, which was then administered to a beagle dog, and the blood concentration of moxidectin was measured. C max-peak n is the Cmax value of the nth injection, C max-peak n+1 is the (n+1)th Cmax value due to the blood concentration of moxidectin increasing again after the nth Cmax value.
[0020] A sustained release injectable composition containing moxidectin according to another embodiment of the present invention may include microparticles containing moxidectin and a suspension solution. Effect of the Invention
[0021] Unlike conventional heartworm preventatives, which have a short half-life and must be administered regularly every month, when microparticles containing moxidectin are administered, moxidectin is released continuously for more than three months, thereby maintaining the preventive effect against heartworms.
[0022] In addition, by producing microparticles having smooth particle properties, a uniform average particle diameter, and a narrow diameter distribution range, it is possible to prevent initial excessive release of moxidectin when the microparticles are administered, and to control the release of the drug so as to maintain a constant concentration of effective moxidectin for more than three months, thereby reducing foreign body sensation and pain when administered as an injection. [Brief description of the drawings]
[0023] [Figure 1] 1 shows an experimental result on the moxidectin release pattern of microparticles according to an embodiment of the present invention. [Diagram 2] 1 shows an experimental result on the moxidectin release pattern of microparticles according to an embodiment of the present invention. [Diagram 3] 1 shows an experimental result on the moxidectin release pattern of microparticles according to an embodiment of the present invention. [Figure 4] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Diagram 5] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 6] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 7] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 8] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 9] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 10] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 11] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 12] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 13] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 14]1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 15] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 16] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 17] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 18] 1 is a SEM measurement photograph of a microparticle according to an embodiment of the present invention. [Figure 19] 1 shows the results of measuring the concentration of moxidectin in the blood of beagle dogs administered with an injection containing microparticles according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present invention relates to microparticles containing moxidectin, the microparticles comprising moxidectin and a biodegradable polymer, the intrinsic viscosity of the biodegradable polymer being 0.1 dl / g to 1 dl / g, and the average diameter of the microparticles being 60 to 110 μm. EXAMPLES
[0025] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, in order to enable those skilled in the art to easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.
[0026] The microparticles containing moxidectin according to one embodiment of the present invention are microparticles containing moxidectin and a biodegradable polymer, and the intrinsic viscosity of the biodegradable polymer may be 0.1 dl / g to 1 dl / g, and the average diameter of the microparticles may be 60 to 110 μm.
[0027] The moxidectin of the present invention is a compound represented by the following chemical formula 1, and means a substance used as a preventive drug for heartworm in animals.
[0028] [ka]
[0029] The microparticles are characterized as being spherical and having a smooth surface.
[0030] The microparticles contain a biodegradable polymer and moxidectin, and are characterized in that the biodegradable polymer and moxidectin are uniformly mixed, and moxidectin is uniformly distributed within the microparticles.
[0031] The microparticles are used in the form of an injection, and can be injected into an animal's body. The microparticles injected into the animal's body can gradually release moxidectin as the biodegradable polymer decomposes.
[0032] Moxidectin is released from the microparticles of the present invention as the biodegradable polymer on the surface is decomposed, and moxidectin begins to be released. Thereafter, when multiple holes are formed inside the microparticles, the moxidectin contained inside the microparticles can be released into the animal's body.
[0033] By releasing moxidectin as described above, the microparticles of the present invention can release moxidectin in the animal's body for 3 months or more, and preferably can release moxidectin continuously for 6 months or 12 months.
[0034] The release of moxidectin may be at or above the concentration range for the treatment or prevention of canine heartworm, which means that moxidectin is not simply released continuously for a long period of time, but is released continuously at or above the blood concentration at which moxidectin can substantially exert its therapeutic effect.
[0035] As described above, the microparticles of the present invention are able to exhibit sustained release of moxidectin and preventive effect against canine heartworms due to the average diameter of the microparticles described above, the coefficient of variation (CV) described below, and the intrinsic viscosity of the biodegradable polymer.
[0036] The microparticles of the present invention may have an average diameter of 60 to 110 μm, 60 to 100 μm, or 70 to 100 μm. When used within the above range, they can exhibit a moxidectin releasing effect for a desired period of time, can be administered without a foreign body sensation when injected, and can prevent absorption by macrophages in the body.
[0037] The microparticles may have a coefficient of variation (CV) of 5% to 20%, 6% to 19%, 7% to 18.5%, or 8% to 18.5%. The coefficient of variation is a value indicating the monodispersity of a particle size distribution diagram, and a smaller CV value means that the particles are more uniform in size.
[0038] The coefficient of variation can be calculated by the following formula 2. [Formula 2] (Standard deviation of diameter / Average diameter)*100
[0039] By including microparticles having a coefficient of variation within the above range, the release pattern of moxidectin can be controlled. In addition, as described below, when the microparticles are produced by the method for producing microparticles of the present invention, microparticles of uniform size can be produced, and therefore microparticles containing different biodegradable polymers can be produced and mixed for use.
[0040] As described above, microparticles containing a drug such as moxidectin can release the drug when the biodegradable polymer is degraded in the body, and therefore the microparticles must be of a uniform size in order to sustainably release the drug for a desired period of time.
[0041] Specifically, when microparticles are distributed in various sizes, small microparticles have the problem that they are quickly decomposed in the body or do not release drugs by macrophages, i.e., even if small microparticles release drugs, they only act in the body at an early stage and are unable to release drugs for a long period of time.
[0042] In addition, when the size of the microparticles is large, the initial drug release effect is small and the drug may be released for an excessively long time. The microparticles are designed to release the drug for a desired period of time, and if the drug is released for more than the desired period of time, the drug release pattern cannot be controlled, which may cause difficulties in repeated administration.
[0043] As described above, the microparticles having various sizes include both small and large microparticles, which means that the size of the microparticles cannot be controlled, which means that the drug release time cannot be controlled, which may cause difficulties in continuous use rather than one-time use.
[0044] The microparticles of the present invention are characterized in that the average particle diameter is 60 to 110 μm and the coefficient of variation is 5% to 20%, which means that the microparticles are distributed within the average diameter range and that only microparticles with a uniform diameter are included.
[0045] By containing uniformly sized microparticles as described above, when injected into an animal's body, it is possible to prevent excessive initial release of moxidectin and exhibit the moxidectin release effect for 3 months, 6 months, or 12 months.
[0046] The biodegradable polymer may be selected from the group consisting of polylactide (PLA), polylactide-co-glycolide (PLGA), polyphosphazenes, polyiminocarbonates, polyphosphoesters, polyanhydrides, polyorthoesters, polycaprolactones, polyhydroxyvalers, polyhydroxybutyrates, polyamino acids, and mixtures thereof.
[0047] The biodegradable polymer may preferably be selected from the group consisting of polylactide (PLA), polylactide-co-glycolide (PLGA), and mixtures thereof.
[0048] Specifically, it may include polylactide (PLA) or polylactide-co-glycolide (PLGA), and may include polylactide (PLA) and polylactide-co-glycolide (PLGA).
[0049] More specifically, the microparticles may contain PLA and moxidectin, may contain PLGA and moxidectin, or may contain PLA, PLGA and moxidectin. The inclusion of all of PLA and PLGA means that when a biodegradable polymer and moxidectin are dissolved in an organic solvent, as described below, all of PLA and PLGA are contained, and the produced microparticles are characterized by the inclusion of all of PLA and PLGA.
[0050] The microparticles of the present invention may also be included in a sustained release injectable composition, as described below, and in this case the microparticles included may be selected from the group consisting of microparticles comprising PLA and moxidectin, microparticles comprising PLGA and moxidectin, microparticles comprising PLA, PLGA and moxidectin, and mixtures thereof.
[0051] The microparticles contained in the injectable composition may contain only one kind of biodegradable polymer, or may contain two or more different kinds of biodegradable polymers, or may contain two or more different kinds of microparticles containing one or more kinds of biodegradable polymers. The inclusion of various kinds of microparticles as described above is for adjusting the release time of moxidectin.
[0052] The intrinsic viscosity of the biodegradable polymer may be 0.1 dl / g to 1 dl / g, 0.1 dl / g to 0.8 dl / g, 0.1 dl / g to 0.7 dl / g, or 0.1 dl / g to 0.6 dl / g. The molecular weight (MW) of the biodegradable polymer may be 10 kg / mol to 100 kg / mol, 11 kg / mol to 80 kg / mol, 12 kg / mol to 70 kg / mol, or 15 kg / mol to 65 kg / mol.
[0053] The microparticles of the present invention are intended to provide a sustained release of moxidectin for 3 months, 6 months or 12 months, preferably for a sustained release of moxidectin in the body of an animal for 6 months or 12 months.
[0054] As explained above, the release of moxidectin from the microparticles is affected not only by the average particle diameter, but also by the intrinsic viscosity. Generally, the greater the viscosity of the biodegradable polymer, the slower the release of moxidectin can be, but this characteristic does not always apply, and the intrinsic viscosity of the biodegradable polymer and the viscosity of moxidectin have an effect on each other, affecting the decomposition of the biodegradable polymer and the release of moxidectin.
[0055] The biodegradable polymers are approved by the FDA and can be used as pharmaceutical injections for the human body, and the decomposition period is specified depending on the type of biodegradable polymer. That is, the biodegradation period of specific polymers is various, such as 2 to 3 months, 6 to 9 months, 10 to 14 months, etc.
[0056] However, this refers to the biodegradation period for the biodegradable polymer, and when this is mixed with moxidectin to produce microparticles, the biodegradation period of the biodegradable polymer may differ due to the effect of moxidectin.
[0057] Therefore, in order to sustainably release moxidectin in the body for a desired period of time, the combination of a biodegradable polymer and moxidectin is important.
[0058] In other words, in order to release moxidectin for three months, it is not enough to simply use a biodegradable polymer with a three-month biodegradation period; it is necessary to consider whether a combination of moxidectin and a biodegradable polymer can achieve biodegradation for three months.
[0059] Therefore, in the present invention, the intrinsic viscosity of the biodegradable polymer is limited to 0.1 dl / g to 1 dl / g, and when a biodegradable polymer having an intrinsic viscosity within this range is used in combination with moxidectin, it is possible to achieve a sustained moxidectin release effect for a desired period of time.
[0060] The microparticles may contain the biodegradable polymer and moxidectin in a weight ratio of 2:1 to 12:1, a weight ratio of 4:1 to 10:1, or a weight ratio of 9:1. When the biodegradable polymer and moxidectin are contained within the above ranges, initial excessive release can be prevented when injected into an animal's body, and the microparticles can exhibit a sustained moxidectin release effect for a desired period of time.
[0061] In the case of typical injectable dosage forms, side effects can occur due to the initial excessive release of moxidectin, but in the present invention, the initial excessive release can be prevented even when the injection is injected, and the moxidectin release effect can be sustained for a desired period of time.
[0062] Furthermore, as explained above, sustained release of moxidectin for 3 months, 6 months, or 12 months means that moxidectin is released at a level that can exhibit a preventive or therapeutic effect against canine heartworms.
[0063] The microparticles may have a molecular weight of 0.3 to 3 according to the following formula 1. [Formula 1] C max-peak n / C max―peak n+1
[0064] Where: Microparticles containing moxidectin were mixed with a suspension solution to prepare an injection, which was then administered to a beagle dog, and the blood concentration of moxidectin was measured. C max-peak n is the Cmax value of the nth injection, C max-peak n+1 is the (n+1)th Cmax value due to the blood concentration of moxidectin increasing again after the nth Cmax value.
[0065] The above formula 1 shows the results of administering the microparticles of the present invention as an injection to beagle dogs and measuring the blood concentration of moxidectin. The value according to the above formula 1 is 0.3 to 3, 0.5 to 3, or may be 0.5 to 2.5. When the ratio of the peak blood concentration value of moxidectin falls within the above range, it is possible to control the long-term release of moxidectin for a desired period of time.
[0066] The above formula 1 indicates the relationship resulting from the appearance of peaks in the blood concentration of moxidectin due to the injectable microparticles containing different biodegradable polymers.
[0067] Specifically, as described above, the microparticles of the present invention can be made of two or more different biodegradable polymers. The microparticles can contain only one type of biodegradable polymer, but can also contain different biodegradable polymers. That is, they can include microparticles containing PLGA and moxidectin and microparticles containing PLA and moxidectin.
[0068] Microparticles containing different biodegradable polymers as described above can exhibit the nth order maximum blood concentration of moxidectin (Cmax-peak n), and then the n+1th order maximum blood concentration of moxidectin (Cmax-peak n+1), as shown in Equation 1.
[0069] The maximum blood concentration of the nth moxidectin is the maximum blood concentration of moxidectin after injection, and means the maximum value in the tendency of the blood concentration value of moxidectin to gradually increase and then decrease again, and the maximum blood concentration of the n+1th moxidectin means the maximum value in the tendency of the blood concentration of moxidectin to increase again and then decrease again after the maximum blood concentration of the nth moxidectin, and the injectable dosage form containing the microparticles of the present invention can show multiple maximum blood concentration values. The maximum blood concentration of the nth moxidectin (Cmax-peak n) and the maximum blood concentration of the n+1th moxidectin (Cmax-peak n+1) can show a value in which the maximum blood concentration of the nth moxidectin is greater than the maximum blood concentration of the n+1th moxidectin, and the maximum blood concentration of the n+1th moxidectin can show a value in which the maximum blood concentration of the nth moxidectin is greater than the maximum blood concentration of the nth moxidectin.
[0070] The above-mentioned tendency of the blood concentration peak changes due to the difference in the release pattern of moxidectin depending on the type of biodegradable polymer. The microparticles of the present invention are produced by the production method described below, and the microparticles produced by the production method of the present invention are characterized in that they can be precisely adjusted to have a uniform particle size. For this reason, microparticles can be produced using different biodegradable polymers and mixed for use.
[0071] As described above, the microparticles prepared using different biodegradable polymers can each exhibit a unique moxidectin release pattern, and multiple blood concentration peaks can appear due to the unique release pattern.
[0072] As explained above, when the microparticles are prepared using different biodegradable polymers, the biodegradation rates of the biodegradable polymers differ. By utilizing this characteristic, a mixture of microparticles capable of releasing early moxidectin and microparticles capable of releasing late moxidectin upon injection can be used to achieve a long-lasting moxidectin release effect.
[0073] In contrast, the microparticles of the present invention are characterized in that, after administration into the body, the maximum blood concentration (Cmax) of moxidectin appears after a specific time point.
[0074] After administration of the microparticles of the present invention, the maximum blood concentration (Cmax) of moxidectin in the body can be affected by the average diameter of the microparticles, the particle size distribution, the type of biodegradable polymer, and the like.
[0075] For example, the microparticles of the 3-month to 6-month dosage form can show a maximum blood concentration (Cmax) within 10 to 90 days after administration into the body. Specifically, the microparticles of the present invention suppress initial excessive release, and after injection into the body, the amount of moxidectin released gradually increases, and after showing a maximum blood concentration within a range of 10 to 90 days, the amount of moxidectin released decreases thereafter, and moxidectin can be continuously released for 3 or 6 months. Unlike the above, when only one type of biodegradable polymer is used, multiple maximum blood concentration peaks of moxidectin do not appear, but only a single maximum blood concentration peak appears, and the maximum blood concentration can appear within a range of 10 to 90 days after injection.
[0076] In addition, in the case of the 12-month dosage form, the maximum blood concentration (Cmax) can be observed between 10 and 90 days, similar to the 3-month and 6-month dosage forms. However, as described above, this can be affected by the average diameter of the microparticles, the particle size distribution, the type of biodegradable polymer, etc.
[0077] The range of dates showing the maximum blood concentration may vary depending on the subject and the dosage, but as in the examples of the present invention, when the total content of moxidectin administered to a beagle is 0.2 mg / kg to 1 mg / kg, the maximum blood concentration of moxidectin (Cmax) can be shown within 10 to 90 days. When the maximum blood concentration of moxidectin (Cmax) is shown within the above range, sustained release of moxidectin is possible for 3 months, 6 months, or 12 months, and preferably for 6 months or 12 months.
[0078] The microparticles containing moxidectin are mixed with a suspension solution to prepare an injection, and the injection is administered to a number of beagle dogs. The same injection is administered in the same manner as in formula 1, and 0.2 mg / kg of moxidectin is administered to 10 beagle dogs. The blood moxidectin concentration of the beagle dogs is measured, and the standard deviation of the blood moxidectin concentration between the beagle dogs at the same time point is 0.01 to 10, 0.01 to 5, or even 0.01 to 3.
[0079] The above-mentioned standard deviation value of the blood moxidectin concentration indicates that the produced microparticles have excellent homogeneity, and the excellent reproducibility of the in vivo experimental results indicates that administration of moxidectin is highly effective and safe.
[0080] Even when the same injection is administered to beagles, the concentration of moxidectin in the blood may vary from dog to dog. This is due to differences in drug metabolizing enzymes between individuals, and even when the same injection is administered, differences may occur in the metabolic rate of the drug released in the body.
[0081] However, in order to provide it as a sustained-release dosage form, it is necessary to control the concentration of moxidectin in the blood so that there are no large differences after administration to the body, and this can be said to be an element that is influenced by the quality of the moxidectin-containing particles produced.
[0082] The microparticles of the present invention are produced by the production method described below, and can be produced to have extremely uniform particle sizes, smooth surfaces, and perfect spheres.
[0083] That is, by producing microparticles having uniform size and properties as described above, even when these are administered as an injection to beagles and the like, some differences in the concentration of moxidectin in the blood may occur due to differences between individuals, but these differences are only minor.
[0084] In contrast, in the case of microparticles that are not uniform in size or have smooth properties, unlike the present invention, the sizes of the microparticles contained in the injection are diverse, and when the injection is administered to a beagle dog or the like, the difference in the blood moxidectin concentration will be large, not only due to the difference between individuals but also due to the difference between the microparticles, due to the difference in properties.
[0085] A sustained release injectable composition containing moxidectin according to another embodiment of the present invention may include microparticles containing moxidectin and a suspension solution.
[0086] The suspension medium comprises an isotonicity agent, a suspending agent and a solvent.
[0087] More specifically, the tonicity agent may be selected from the group consisting of D-Mannitol, Maltitol, Sorbitol, Lactitol, Xylitol, Sodium chloride, and mixtures thereof, preferably D-Mannitol, but is not limited to the above examples.
[0088] The suspending agent may be sodium carboxymethylcellulose, polysorbate 80, starch, starch derivatives, polyhydric alcohols, chitosan, chitosan derivatives, cellulose, cellulose derivatives, collagen, gelatin, hyaluronic acid (HA), alginic acid, algin, pectin, carrageenan, chondroitin, chondroitin sulfate, dextran, dextran sulfate, polylysine, titin, fibrin, agarose, fluran, xanthan gum, etc. gum), and mixtures thereof, preferably sodium carboxymethylcellulose and polysorbate 80, but not limited to the above examples.
[0089] The solvent may be water for injection, and any solvent that can be used as water for injection may be used without limitation.
[0090] Another embodiment of the present invention provides a method for producing microparticles containing moxidectin, comprising the steps of: 1) dissolving a biodegradable polymer and moxidectin in an organic solvent to produce an oil phase solution; 2) dissolving a surfactant in water to produce an aqueous phase solution; 3) injecting and flowing the oil phase solution of step 1) into a microchannel in a linear direction; and 4) injecting and flowing the aqueous phase solution of step 2) into a microchannel formed on both sides or one side so as to form an intersection with the microchannel in which the oil phase solution of step 3) flows in a linear direction, thereby forming a microchannel in which the oil phase solution of step 3) flows in a linear direction. The method includes the steps of: producing microparticles uniformly containing moxidectin by intersecting a flow of the solution with a flow of an aqueous phase solution; 5) collecting the microparticles produced at the intersection of step 4); 6) stirring the microparticles collected in step 5) to evaporate and remove the organic solvent present in the microparticles; and 7) washing and drying the microparticles of step 6), wherein the intrinsic viscosity of the biodegradable polymer is 0.1 dl / g to 1 dl / g, and the average particle diameter of the microparticles may be 60 to 110 μm.
[0091] Step 1) is a step of preparing an oil phase solution, in which moxidectin and a biodegradable polymer are dissolved in an organic solvent to prepare an oil phase solution. The biodegradable polymer is polylactide (PLA), preferably polylactide-co-glycolide (PLGA) or polylactide (PLA), but is not limited to these examples.
[0092] The organic solvent is immiscible with water, and is, for example, any one or more selected from the group consisting of chloroform, chloroethane, dichloroethane, dichloromethane, trichloroethane, and mixtures thereof. Dichloromethane is preferred, but is not limited to this example. It can be said that any organic solvent that can dissolve biodegradable polymers and moxidectin and that can be easily selected by a person skilled in the art is usable, without being limited to the above examples.
[0093] Step 1) is to prepare an oil phase solution in which moxidectin and a biodegradable polymer are dissolved, and as described above, an organic solvent is used as the solvent. This is done by using the solubility properties of moxidectin and a biodegradable polymer to completely dissolve them using an organic solvent. More specifically, moxidectin and a biodegradable polymer are dissolved in an organic solvent to prepare an oil phase solution.
[0094] The weight ratio of the biodegradable polymer and moxidectin in the oil phase solution is 2:1 to 12:1, 4:1 to 10:1, or may be 9:1. When used in a mixture within the above range, moxidectin can be released continuously for a long period of time due to the decomposition of the biodegradable polymer.
[0095] If the weight ratio of moxidectin to biodegradable polymer is less than 1:2, i.e., if the biodegradable polymer is contained in a ratio less than this range, the weight ratio of the biodegradable polymer compared to the weight of moxidectin will be small, making it difficult to produce microparticles in which moxidectin is uniformly distributed in spherical biodegradable polymer particles. If the weight ratio of biodegradable polymer to moxidectin is more than 1:12, i.e., if the biodegradable polymer is contained in a ratio greater than this range, the content of moxidectin in the sustained release particles will be low, making it necessary to administer a large amount of sustained release particles to administer the drug at the desired concentration.
[0096] More specifically, the biodegradable polymer in the oil phase solution is contained in an amount of 10 to 20% by weight, and preferably 15% by weight, but is not limited to this example.
[0097] The step 2) is a step of preparing an aqueous phase solution, and a surfactant is dissolved in water to prepare the aqueous phase solution. The surfactant can be used without limitation as long as it can assist the biodegradable polymer solution in forming a stable emulsion. Specifically, the surfactant is any one or more selected from the group consisting of nonionic surfactants, anionic surfactants, cationic surfactants, and mixtures thereof, and more specifically, any one or more selected from the group consisting of methylcellulose, polyvinylpyrrolidone, lecithin, gelatin, polyvinyl alcohol, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene castor oil derivatives, sodium lauryl sulfate, sodium stearate, esteramines, linear diamines, aliphatic amines, and mixtures thereof, and preferably polyvinyl alcohol, but is not limited to the above.
[0098] The surfactant contained in the aqueous phase solution may be 0.1 to 1.0% by weight, 0.2 to 0.5% by weight, or 0.25% by weight, with the remainder being all water.
[0099] The step 3) is a step of injecting and flowing the oil phase solution and the aqueous phase solution into a microchannel formed on a wafer or an organic substrate.
[0100] The conventional microchannel used to manufacture the same microparticles as those of the present invention was manufactured by forming seven microchannels on a silicon wafer. The microchannels include a channel for flowing an aqueous phase solution, a channel for flowing an oil phase solution, and a channel through which the emulsion generated after the aqueous phase solution and the oil phase solution form an intersection moves.
[0101] However, in the case of the conventional chip in which a total of seven channels are formed on a silicon wafer, a small number of microchannels are formed, and when microparticles are simultaneously produced using the seven microchannels, it is possible to produce microparticles of the same size by adjusting the oil pressure of the oil phase solution and the aqueous phase solution.
[0102] However, as the number of microchannels formed in the chip increases, it becomes difficult to manufacture uniformly sized microparticles by controlling the oil pressure of the oil phase solution and the aqueous phase solution.
[0103] That is, when 10 or more microchannels are formed on one plane, it is not easy to supply the same hydraulic pressure to the aqueous phase solution and the oil phase solution from the first channel to the tenth channel, and the uneven distribution of hydraulic pressure in each microchannel causes problems such as different sizes and particle size distributions of the produced microparticles.
[0104] Therefore, the present invention is characterized in that the flow rate ratio of the fluids flowing into the channels of the oil phase solution and the aqueous phase solution is maintained at 1:45 or more, in order to enable the production of uniformly sized microparticles even in a chip having 10 or more microchannels.
[0105] Specifically, when the flow rate of the oil phase solution is adjusted to 110 μl / min, and the flow rate of the aqueous phase solution is 5,000 μl / min, a uniform emulsion can be produced at the intersection.
[0106] The production of microparticles using microchannels as described above utilizes microfluidics, which is a technology for producing microparticles having a uniform diameter distribution using microfluidics technology, and is a technology that uses the polarity difference between an oil phase solution and an aqueous phase solution to generate an emulsion due to the repulsive force between the fluids when passing through a micro-channel.
[0107] When using existing chips with a single channel or around 10 channels, it was possible to control the flow rate by adjusting the pressure (air pressure) ratio of the oil phase solution and aqueous phase solution injected into the channel. However, when using an integrated chip with multiple channels, it is important to adjust the flow rate ratio of the oil phase solution and aqueous phase solution, rather than the pressure of the oil phase solution and aqueous phase solution injected into the channel.
[0108] The flow rate ratio of the oil phase solution and the aqueous phase solution determines whether or not microparticles can be produced using a microchannel. When the fluid flowing through the microchannel forms a laminar flow and is uniformly cut off at the junction where the channels meet due to the repulsive force of the fluid, this indicates a dripping condition. However, when the flow rate ratio of the oil phase solution and the aqueous phase solution is outside the range of the present invention, a jetting phenomenon, not dripping, occurs and a uniform emulsion cannot be produced.
[0109] FIG. 1 is a photograph of an emulsion formed when the aqueous phase solution and the oil phase solution are within a range of flow rate ratios according to an embodiment of the present invention, showing dripping conditions at the intersection where the channels meet.
[0110] It can be seen that the emulsion shown in FIG. 1 has particles with a uniform size of 170 to 190 μm, perfectly spherical, and with a smooth surface.
[0111] In contrast, Figure 2 shows the dripping conditions at the intersection of the channels and a conceptual diagram of the emulsion that can be formed by the jetting phenomenon.
[0112] As described above, when dripping is performed, it can be seen that an emulsion having a uniform diameter is formed as shown in FIG. 1, but when jetting is performed, it can be seen that an emulsion having a different diameter is formed.
[0113] The flow rate ratio of the oil phase solution and the aqueous phase solution is 1:45 or more, and may be 1:45 to 1:125. If it is less than 1:45, it is jetted and cannot have a uniform size distribution with a CV of 10% or less, and if the ratio of the aqueous phase is greater than 1:45 and is 1:125 or more, it is completely dripped and has a suitable size distribution, but as the ratio of the aqueous phase increases, the amount of aqueous phase solution used increases, which may cause problems in production volume.
[0114] More specifically, the microchannel may be formed in a material selected from the group consisting of a glass substrate, a silicon wafer, or a polymer film, but examples of the material are not limited to the above examples, and any material capable of forming a microchannel can be used.
[0115] The polymer film may be selected from the group consisting of, but is not limited to, polyimide, polyethylene, fluorinated ethylene propylene, polypropylene, polyethylene terephthalate, polyethylene naphthalate, polysulfone, and mixtures thereof.
[0116] For example, aluminum is deposited on a silicon wafer using an e-beam evaporator, and photoresist is patterned on the aluminum using photolithography. Then, the aluminum is etched using the photoresist as a mask, and after removing the photoresist, silicon is etched by DRIE (deep ion reactive etching) using the aluminum as a mask. After removing the aluminum, glass is anodically bonded on the wafer and sealed to manufacture the microchannel.
[0117] The microchannel has an average diameter of 160 to 200 μm, preferably 180 μm, but is not limited to this example. If the average diameter of the microchannel is 160 μm or less, the diameter of the microparticles produced may be smaller than 50 μm, which may affect effective drug release and in vivo absorption. If the average diameter of the microchannel is 200 μm or more, the average size of the produced microparticles may exceed 120 μm, which may increase foreign body sensation and pain when administered as an injection, and the larger the diameter of the microchannel, the larger the particle size distribution of the produced particles, making it difficult to produce microparticles of uniform particle size.
[0118] In addition, the average diameter of the microchannel is closely related to the average diameter of the particles, and is also closely related to the flow rate ratio (μl / min) of the oil phase solution and the aqueous phase solution.
[0119] The cross-sectional width (w) and cross-sectional height (d) of the microchannel are closely related to the average diameter (d') of the produced microparticles. The cross-sectional width (w) of the microchannel is in a ratio range of 0.7 to 1.3 to the average diameter (d') of the microparticles, and the cross-sectional height (d) of the microchannel is in a ratio range of 0.7 to 1.3 to the average diameter (d') of the microparticles.
[0120] In other words, once the average diameter (d') of the microparticles to be produced is determined, the width (w) and height (d) of the cross section of the microchannel must be set within a ratio range of 0.7 to 1.3 of d' in order to produce microparticles of the desired size.
[0121] The step 3) involves flowing the oil phase solution and the aqueous phase solution through the first microchannel and the second microchannel formed at the intersection under the flow rate conditions.
[0122] That is, the oil phase solution flows along a first microchannel, and the aqueous phase solution flows along a second microchannel shaped to form an intersection with the first microchannel, where it meets the flow of the oil phase solution.
[0123] More specifically, when the oil phase solution is injected into the first microchannel, the flow rate ratio of the oil phase solution to the aqueous phase solution when the aqueous phase solution is injected into the second microchannel is 1:45 or more, and may be 1:45 to 1:125.
[0124] As explained above, conventional microparticles could be manufactured by controlling hydraulic pressure to produce microparticles with a uniform diameter, but in the case of a chip with 10 or more microchannels integrated, it was impossible to manufacture microparticles with a uniform diameter by controlling hydraulic pressure. Therefore, by adjusting the flow rate ratio of the oil phase solution and the aqueous phase solution, it is possible to manufacture microparticles with a uniform diameter.
[0125] As described above, when the flow rates of the oil phase solution and the aqueous phase solution are made different, the aqueous phase solution having a relatively larger flow rate compresses the oil phase solution at the point where the oil phase solution flow meets the aqueous phase solution flow, and at this time, a dripping phenomenon occurs due to the repulsive force between the oil phase solution and the aqueous phase solution, producing spherical microparticles in which the biodegradable polymer and moxidectin are uniformly distributed. More specifically, the microparticles form microparticles in which moxidectin is uniformly distributed on a spherical biodegradable polymer.
[0126] The step 4) is a step of collecting the microparticles, and the microparticles are collected in a water bath containing an aqueous phase solution to prevent aggregation between the initially generated microparticles.
[0127] Step 4) is used to prevent the collected microparticles from clumping together by using the aqueous phase solution prepared in step 2), i.e., a mixed solution of surfactant and water, and then injecting a portion of the aqueous phase solution into the microchannel and transferring the other portion to the water tank in step 4).
[0128] The step 5) is a step for removing the organic solvent present in the microparticles collected in the water tank, and the organic solvent present inside the microparticles is evaporated and removed by stirring under a certain temperature condition and stirring speed. At this time, the stirring conditions are 5-1) a step of primary stirring at a speed of 150-350 rpm for 50-70 minutes at 15-20°C, 5-2) a step of secondary stirring at a speed of 250-450 rpm for 50-70 minutes at 20-30°C, and 5-3) a step of tertiary stirring at a speed of 450-650 rpm for 3-9 hours at 40-60°C.
[0129] The stirring speed is set to different temperature conditions and stirring progress times for the primary and secondary stirring steps to progress the stirring process.
[0130] As described above, the temperature condition is increased in the second stirring step compared to the first stirring step, and the temperature is increased stepwise to control the evaporation rate of the organic solvent present inside the microparticles, i.e., the organic solvent present inside the microparticles is gradually evaporated to produce the microparticles.
[0131] The temperature of the oil phase solution and the aqueous phase solution when they flow through the microchannel is also 15 to 20°C, and preferably 17°C. That is, after they flow through the microchannel and form an intersection to generate microparticles, the low temperature is kept constant at 15 to 20°C until the collected microparticles are first stirred. Only by maintaining a low temperature during the microparticle production process can spherical particles be produced and maintained. That is, if the temperature is not low, problems occur in which it is difficult to produce uniform spherical particles.
[0132] Thereafter, the second stirring process gradually increases the temperature and increases the stirring time, so that the organic solvent present inside the microparticles gradually moves to the surface, and the organic solvent evaporates from the surface, thereby minimizing the influence on the properties of the microparticles. That is, if the organic solvent evaporates rapidly, the surface of the microparticles may not be smooth due to the evaporation of the organic solvent, and pores may be formed. In order to prevent this problem, the temperature condition is gradually increased as described above, and the time for which the stirring process is performed is also increased, so that the evaporation rate of the organic solvent can be controlled, and the surface properties of the manufactured microparticles can be controlled by controlling the evaporation rate of the organic solvent.
[0133] In the tertiary stirring step, after the organic solvent in the emulsion is extracted as an external aqueous phase, the external aqueous phase is heated to a temperature close to the boiling point of the organic solvent and stirred, thereby removing the saturated organic solvent from the aqueous phase and facilitating the removal of the residual organic solvent within the microparticles.
[0134] Finally, step 6) is a step of washing and drying the microparticles. After stirring to remove all organic solvent from the surface of the microparticles, the microparticles are washed several times with sterilized and filtered purified water to remove any surfactant remaining on the microparticles, and then freeze-dried.
[0135] The finally produced microparticles are in the form of spherical microparticles made of biodegradable polymers in which moxidectin is uniformly distributed, and contain the biodegradable polymer and moxidectin in a weight ratio of 2:1 to 12:1.
[0136] The weight ratio of moxidectin and biodegradable polymer contained in the microparticles is the same as the weight ratio in the oil phase solution, and this is achieved by producing oil phase emulsion particles by passing through a microchannel and removing all of the organic solvent in the emulsion, thereby producing microparticles containing moxidectin and biodegradable polymer in the same weight ratio as in the oil phase solution.
[0137] Manufacturing Example 1 Production of microparticles containing moxidectin Polylactide-co-glycolide (PLGA) having a viscosity of 0.2 dl / g, containing terminal carboxylic acid groups, having a molecular weight (MW) of 17 kg / mol, and having a lactide to glycolide ratio of 75:25, and moxidectin were dissolved in dichloromethane to prepare an oil phase solution, in which the polylactide-co-glycolide in the oil phase solution was contained at a ratio of 15 wt%, and the weight ratio of polylactide-co-glycolide to moxidectin was 9:1.
[0138] Polyvinyl alcohol, a surfactant, was mixed with water to prepare an aqueous solution containing 0.25% by weight of polyvinyl alcohol.
[0139] The oil phase solution and the aqueous phase solution were injected into a microchannel formed on a silicon wafer, and the oil phase solution and the aqueous phase solution were injected into each microchannel at a flow rate ratio of 1:50 and maintained at a temperature of 17°C.
[0140] The microparticles generated at the intersection where the oil phase solution flow and the aqueous phase solution flow meet were collected in a water bath containing a second mixture, which was first stirred at 250 rpm at 17° C. for 1 hour, second stirred at 350 rpm at 25° C. for 1 hour, and then heated to 55° C. and third stirred at 550 rpm for 4 hours.
[0141] After stirring, the microparticles were washed several times with sterilized and filtered purified water and freeze-dried to produce microparticles.
[0142] Manufacturing Example 2-1 Microparticles were prepared in the same manner as in Preparation Example 1, except that polylactic acid having a viscosity of 0.2 dl / g, containing terminal carboxyl groups, and a molecular weight (MW) of 17 kg / mol was used instead of polylactide-co-glycolide.
[0143] Manufacturing Example 2-2 Microparticles were prepared in the same manner as in Preparation Example 1, except that polylactic acid having a viscosity of 0.2 dl / g, containing terminal carboxyl groups, and a molecular weight (MW) of 17 kg / mol was used instead of polylactide-co-glycolide, and the content of polylactic acid in the oil phase solution was 10 wt %.
[0144] Manufacturing Example 3-1 Microparticles were prepared in the same manner as in Preparation Example 1, except that polylactic acid having a viscosity of 0.4 dl / g, containing terminal carboxyl groups, and a molecular weight (MW) of 45 kg / mol was used instead of polylactide-co-glycolide.
[0145] Manufacturing Example 3-2 Microparticles were prepared in the same manner as in Preparation Example 1, except that polylactic acid having a viscosity of 0.4 dl / g, containing terminal carboxyl groups, and a molecular weight (MW) of 45 kg / mol was used instead of polylactide-co-glycolide, and the content of polylactic acid in the oil phase solution was 10 wt %.
[0146] Production Example 4 Microparticles were prepared in the same manner as in Preparation Example 1, except that polylactic acid having a viscosity of 0.4 dl / g, containing terminal ester groups, and a molecular weight (MW) of 45 kg / mol was used instead of polylactide-co-glycolide, and the content of polylactic acid in the oil phase solution was 10 wt %.
[0147] Production Example 5 Microparticles were prepared in the same manner as in Preparation Example 1, except that polylactic acid having a viscosity of 0.5 dl / g, containing terminal ester groups, and a molecular weight (MW) of 61 kg / mol was used instead of polylactide-co-glycolide, and the content of polylactic acid in the oil phase solution was 10 wt %.
[0148] Production Example 6 As biodegradable polymers, polylactide-co-glycolide (PLGA) having a viscosity of 0.2 dl / g, containing terminal carboxyl groups, a molecular weight (MW) of 17 kg / mol, and a lactide to glycolide ratio of 75:25, and polylactide (PLA) having a viscosity of 0.2 dl / g, containing terminal carboxyl groups, and a molecular weight (MW) of 17 kg / mol were used, the weight ratio of the PLGA and PLA was 1:1, and the polylactide-co-glycolide and polylactic acid in the oil phase solution were contained in a ratio of 10 wt%. Microparticles were produced in the same manner as in Production Example 1.
[0149] Manufacturing Example 7-1 As biodegradable polymers, polylactide (PLA) having a viscosity of 0.2 dl / g, terminal carboxyl groups, and a molecular weight (MW) of 17 kg / mol, and polylactide (PLA) having a viscosity of 0.4 dl / g, terminal carboxyl groups, and a molecular weight (MW) of 45 kg / mol were used, and microparticles were prepared in the same manner as in Preparation Example 1, except that the weight ratio of the different PLAs was 1:1.
[0150] Manufacturing Example 7-2 As biodegradable polymers, polylactide (PLA) having a viscosity of 0.2 dl / g, terminal carboxyl groups, and a molecular weight (MW) of 17 kg / mol, and polylactide (PLA) having a viscosity of 0.4 dl / g, terminal carboxyl groups, and a molecular weight (MW) of 45 kg / mol were used, the weight ratio of the different PLAs was 1:1, and the total polylactic acid in the oil phase solution was 10 wt%. Microparticles were produced in the same manner as in Production Example 1, except that the weight ratio of the different PLAs was 1:1.
[0151] Production Example 8 As biodegradable polymers, polylactide (PLA) having a viscosity of 0.2 dl / g, terminal carboxyl groups, and a molecular weight (MW) of 17 kg / mol, and polylactide (PLA) having a viscosity of 0.4 dl / g, terminal ester groups, and a molecular weight (MW) of 45 kg / mol were used, the weight ratio of the different PLAs was 1:1, and the total polylactic acid in the oil phase solution was 10 wt%. Microparticles were produced in the same manner as in Production Example 1, except that the weight ratio of the different PLAs was 1:1.
[0152] Manufacturing Example 9-1 As biodegradable polymers, polylactide (PLA) having a viscosity of 0.2 dl / g, terminal carboxyl groups, and a molecular weight (MW) of 17 kg / mol, and polylactide (PLA) having a viscosity of 0.4 dl / g, terminal carboxyl groups, and a molecular weight (MW) of 45 kg / mol were used, and microparticles were prepared in the same manner as in Preparation Example 1, except that the weight ratio of the different PLAs was 1:3.
[0153] Manufacturing Example 9-2 As biodegradable polymers, polylactide (PLA) having a viscosity of 0.2 dl / g, terminal carboxyl groups, and a molecular weight (MW) of 17 kg / mol, and polylactide (PLA) having a viscosity of 0.4 dl / g, terminal carboxyl groups, and a molecular weight (MW) of 45 kg / mol were used, the weight ratio of the different PLA was 1:3, and the total polylactic acid in the oil phase solution was 10 wt%. Microparticles were produced in the same manner as in Production Example 1, except that the weight ratio of the different PLA was 1:3.
[0154] Manufacturing Example 10 As biodegradable polymers, polylactide (PLA) having a viscosity of 0.4 dl / g, terminal ester groups, and a molecular weight (MW) of 45 kg / mol, and polylactide (PLA) having a viscosity of 0.5 dl / g, terminal ester groups, and a molecular weight (MW) of 61 kg / mol were used, the weight ratio of the different PLAs was 1:1, and the total polylactic acid in the oil phase solution was 10 wt%. Microparticles were produced in the same manner as in Production Example 1, except that the weight ratio of the different PLAs was 1:1.
[0155] Manufacturing Example 11 As biodegradable polymers, polylactide-co-glycolide (PLGA) having a viscosity of 0.2 dl / g, containing terminal carboxyl groups, having a molecular weight (MW) of 17 kg / mol, and having a lactide to glycolide ratio of 50:50, polylactide-co-glycolide (PLGA) having a viscosity of 0.2 dl / g, containing terminal carboxyl groups, having a molecular weight (MW) of 17 kg / mol, and having a lactide to glycolide ratio of 75:25, and polylactide (PLA) having a viscosity of 0.2 dl / g, containing terminal carboxyl groups, and having a molecular weight (MW) of 17 kg / mol were used, and microparticles were prepared in the same manner as in Preparation Example 1, except that the weight ratio of each of the different polymers was 1:1:4.
[0156] Example 1 The microparticles of Preparation Example 1 and the microparticles of Preparation Example 2-1 were mixed in a weight ratio of 1:2, and 2.0 mL of a suspension solvent was added per vial, followed by uniformly suspending the mixture to prepare a composition for subcutaneous injection.
[0157] The suspension solvent had the composition shown in Table 1 below. [Table 1]
[0158] Example 2 A composition for subcutaneous injection was prepared in the same manner as in Example 1, except that the microparticles of Preparation Example 1 and the microparticles of Preparation Example 2-1 were mixed in a weight ratio of 1:1 and used.
[0159] Example 3 The experiment was carried out in the same manner as in Example 1, except that 50% of the dose administered in Example 1 was administered. In the same manner, the microparticles of Preparation Example 1 and the microparticles of Preparation Example 2-1 were mixed in a weight ratio of 1:2 and administered.
[0160] Experimental Example 1 Release pattern In order to confirm the release of moxidectin from the microparticles of Preparation Examples 1, 2-1, 4 and 5, a release experiment was carried out.
[0161] The release test liquid used in the release experiment was a solution containing 2% Tween 20 in purified water. 100 mg of microparticles were placed in an injection vial containing 100 ml of the release test liquid, sealed, and then stirred and shaken at 55°C and 120 rpm to confirm the difference in dissolution rate.
[0162] The experimental results are shown in Figure 1.
[0163] The microparticles of Preparation Example 1 release 50% of moxidectin after 15 hours and are applicable to a 3-month dosage form, while the microparticles of Preparation Example 2-1 release 50% of moxidectin after 20 hours and are applicable to a 6-month dosage form.
[0164] The microparticles of Preparation Example 4 release 50% of moxidectin after 84 hours, and can be used in a dosage form that releases moxidectin for a longer period of time than Preparation Examples 1 and 2-1.
[0165] In addition, it can be confirmed that the microparticles of Preparation Example 5 take a longer time to release 50% of moxidectin compared to the microparticles of Preparation Example 3.
[0166] Experimental Example 2 Release pattern In order to confirm the release of moxidectin from the microparticles of Preparation Examples 2-1, 3-1, 9-1, 7-1 and 11, a release experiment was carried out.
[0167] The release test liquid used in the release experiment was a solution containing 2% Tween 20 and 0.001M sodium bicarbonate in purified water. 100 mg of microparticles were placed in an injection vial containing 100 ml of the release test liquid, which was then sealed and stirred and shaken at 55°C and 120 rpm to confirm the difference in dissolution rate.
[0168] The experimental results are shown in Figure 2.
[0169] In a release test of microparticles of similar size with a mean diameter (MV) of around 95μm, the release pattern differed depending on the molecular weight of the polymer that made up the microparticles. When comparing the release rates of the microparticles of Preparation Examples 2-1, 3-1, 7-1 and 9-1, it was found that the higher the ratio of polylactide with a molecular weight (MW) of 45kg / mol in the microparticles compared to polylactide with a molecular weight (MW) of 17kg / mol, the longer the application of the formulation to moxidectin release.
[0170] In Preparation Examples 7-1 and 9-1, it was confirmed that the release delay time differed depending on the ratio of polylactide having a molecular weight (MW) of 17 kg / mol to polylactide having a molecular weight (MW) of 45 kg / mol, which was 1:1 to 1:3.
[0171] In addition, it can be confirmed that the microparticles of Preparation Example 11 contain polylactide-co-glycolide (PLGA) compared to the microparticles of the other Preparation Examples, and therefore release moxidectin more rapidly.
[0172] Experimental Example 3 Release pattern In order to confirm the release of moxidectin from the microparticles of Preparation Examples 2-2, 3-2, 4, 7-2, 8 and 9-2, a release experiment was carried out.
[0173] The release test liquid used in the release experiment was a solution containing 2% Tween 20 and 0.001M sodium bicarbonate in purified water. 100 mg of microparticles were placed in an injection vial containing 100 ml of the release test liquid, which was then sealed and stirred and shaken at 55°C and 120 rpm to confirm the difference in dissolution rate.
[0174] The experimental results are shown in Figure 3.
[0175] In release tests of microparticles of similar size with a mean diameter (MV) of around 85μm, the release pattern differed depending on the ratio of molecular weights of the polymers that make up the microparticles and the difference in polymer end groups. When comparing the release rates of the microparticles of each manufacturing example, the higher the ratio of polylactide with a molecular weight (MW) of 45kg / mol in the microparticles is compared to polylactide with a molecular weight (MW) of 17kg / mol, the longer it can be applied to a dosage form that releases moxidectin.
[0176] In addition, when comparing the microparticles of Preparation Examples 3-2 and 3-4, it can be confirmed that the release of moxidectin is more delayed when the terminal group contains an ester group rather than a carboxyl group.
[0177] Experimental Example 4 Results of PSA analysis In order to specifically confirm the diameter of the microparticles, an analysis was carried out for Preparation Examples 1 to 11 using a Microtrac particle size analyzer.
[0178] The unit of D10 to D90 is μm, and CV (%) was calculated as SD / Mean*100.
[0179] It is calculated as the span value (D90-D10) / D50 and indicates the uniformity of particle size distribution.
[0180] The results of particle size analysis for the Preparation Examples are shown in Table 2 below. [Table 2]
[0181] According to Table 2, the microparticles according to the preparation examples of the present invention have D50s of 84.85 μm, 90.70 μm, 83.69 μm, 91.41 μm, 82.38 μm, 87.92 μm, 84.20 μm and 79.98 μm, and the CV values are 14.46%, 10.43%, 9.49%, 10.97%, 8.98%, 11.35%, 12.91% and 11.27%, confirming a uniform particle distribution.
[0182] In addition, it can be confirmed that the mean particle diameters (MV) of the microparticles are 90.85 μm, 93.29 μm, 85.26 μm, 96.05 μm, 86.67 μm, 89.51 μm, 87.22 μm and 81.87 μm, showing a uniform particle distribution within the range of 70 to 100 μm.
[0183] The results of particle size analysis for Production Examples 7-1 to 11 are shown in Table 3 below. [Table 3]
[0184] According to Table 3, the microparticles according to the preparation examples of the present invention have D50s of 98.5 μm, 80.46 μm, 91.23 μm, 95.64 μm, 84.5 μm, 78.52 μm and 93.32 μm, and the CV values are 11.13%, 6.74%, 10.53%, 10.75%, 10.64%, 10.63% and 9.46%, respectively, confirming a uniform particle distribution.
[0185] In addition, it can be confirmed that the mean particle diameters (MV) of the microparticles are 99.63 μm, 80.54 μm, 91.22 μm, 96.96 μm, 86.72 μm, 78.61 μm and 93.04 μm, showing a uniform particle distribution within the range of 70 to 100 μm.
[0186] According to the results of the PSA analysis in Tables 2 and 3, when the polymer in the oil phase solution was contained at a ratio of 10 wt%, the mean particle size (MV) of the particles was confirmed to be 84.96 on average with a standard deviation of 4.17, and when the polymer in the oil phase solution was contained at a ratio of 15 wt%, the mean particle size (MV) of the particles was confirmed to be 94.97 μm on average with a standard deviation of 3.17, indicating that the mean particle size (MV) of the particles increases as the concentration of the polymer in the oil phase solution increases.
[0187] In addition, the particles according to each manufacturing example have a Span value indicating the particle size distribution of 0.5 or less and a CV (%) within 5 to 20%, which indicates that the particles manufactured by the above manufacturing methods have a very uniform particle size distribution.
[0188] The results of particle size analysis of the produced microparticles according to the polymer content in the oil phase solution are shown in Table 4 below. [Table 4]
[0189] According to the results of the PSA analysis in the table, when the polymer in the oil phase solution made of the same polymer (PLGA) is contained in a ratio of 5 wt%, the average particle size (MV) of each particle is 57.98, when the polymer in the oil phase solution is contained in a ratio of 10 wt%, the average particle size (MV) of each particle is 76.27 on average, when the polymer in the oil phase solution is contained in a ratio of 15 wt%, the average particle size (MV) of each particle is 93.14 on average, and when the polymer in the oil phase solution is contained in a ratio of 20 wt%, the average particle size (MV) of each particle is 103.30 on average. It can be seen that the average particle size (MV) of the particles increases as the concentration of the polymer in the oil phase solution increases.
[0190] Therefore, when the flow rate ratio of the oil phase to the water phase is kept constant under dripping conditions using the same microchannel, microparticles of the desired particle size can be produced by changing the weight percentage of the polymer that constitutes the oil phase liquid. This makes it possible to control the drug release pattern depending on the size of the microparticles, such as suppressing the initial burst, and can be used to set the drug retention period.
[0191] Experimental Example 5 Results of SEM analysis In order to specifically confirm the properties of the microparticles, Preparation Examples 1 to 11 were analyzed using a Scanning Electron Microscope (SEM).
[0192] The results of SEM analysis for Production Examples 1 to 11 are shown in the following Figures 3 to 18.
[0193] SEM images confirmed that the particles were uniform in size and had perfectly spherical microparticles with smooth surfaces.
[0194] Experimental Example 6 Pharmacokinetic analysis results The pharmacokinetic evaluation for Example 1 was confirmed.
[0195] The above Example 1 was a sustained release formulation for 6 months or more, and it was confirmed whether the efficacy of moxidectin could be maintained by continuously releasing moxidectin for 6 months after injection.
[0196] The amount of moxidectin administered to beagle dogs using the microparticles of the present invention was 0.4 mg / kg, and was administered via SC injection to a total of five dogs.
[0197] The results of the moxidectin blood concentration analysis are shown in Table 5 below. [Table 5]
[0198] According to the experimental results, it was confirmed that there was no initial excessive release of moxidectin in the blood concentration, and the first Cmax was observed around 25 days after injection. After 25 days, the moxidectin blood concentration steadily decreased, and after 56 days, the moxidectin blood concentration increased. Thereafter, the second Cmax was observed around 91 days. Therefore, it can be confirmed that the value according to the following formula 1 is 1.35. [Formula 1] C max-peak n / C max―peak n+1
[0199] Where: Microparticles containing moxidectin were mixed with a suspension solution to prepare an injection, which was then administered to a beagle dog, and the blood concentration of moxidectin was measured. C max-peak n is the Cmax value of the nth injection, C max-peak n+1 is the (n+1)th Cmax value due to the blood concentration of moxidectin increasing again after the nth Cmax value.
[0200] This blood concentration pattern of moxidectin is achieved by producing microparticles using two types of biodegradable polymers, which are then mixed together to produce an injectable dosage form. Differences in decomposition rate occur depending on the viscosity and molecular weight of the biodegradable polymer and its combination with moxidectin, resulting in the above-mentioned blood concentration release pattern.
[0201] The pharmacokinetic properties of Example 1 are shown in Table 6 below. [Table 6]
[0202] Experimental Example 7 Pharmacokinetic analysis results The pharmacokinetic evaluation for Example 2 was confirmed.
[0203] The experiment was carried out in the same manner as in Example 1, except that the microparticles of Preparation Example 1 and the microparticles of Preparation Example 2-1 were mixed in a weight ratio of 1:1. [Table 7]
[0204] According to the experimental results, it was confirmed that there was no initial excessive release of moxidectin in the blood concentration, and the first Cmax was observed around 21 days after injection. After 21 days, the moxidectin blood concentration steadily decreased, and after 56 days, the moxidectin blood concentration increased. Thereafter, the second Cmax was observed around 70 days. Therefore, it can be confirmed that the value according to the above formula 1 is 2.24.
[0205] Furthermore, 24 hours after injection, the blood concentration of moxidectin was 0.75 ng / ml, and the standard deviation of the blood concentration in the beagle dogs undergoing the experiment was 0.24.
[0206] The results of the analysis of the pharmacokinetic properties of Example 2 are shown in Table 8 below. [Table 8]
[0207] Experimental Example 8 Pharmacokinetic analysis results Pharmacokinetic evaluation for Example 3 was underway.
[0208] The experiment was carried out in the same manner as in Example 1, except that 50% of the dose administered in Example 1 was administered. In the same manner, the microparticles of Preparation Example 1 and the microparticles of Preparation Example 2-1 were mixed in a weight ratio of 1:2 and administered. [Table 9]
[0209] According to the experimental results, it was confirmed that there was no initial excessive release of moxidectin in the blood, and the first Cmax was observed around 35 days after injection. After 35 days, the moxidectin blood concentration steadily decreased, and after 77 days, the moxidectin blood concentration increased. Thereafter, the second Cmax was observed around 105 days. Therefore, it can be confirmed that the value according to the above formula 1 is 0.56.
[0210] Experimental Example 9 Pharmacokinetic analysis results In in vivo experiments, the blood moxidectin concentrations of different animals were compared to confirm reproducibility when the same test drug was administered.
[0211] For comparison, the currently commercially available ProHeart SR-12 was administered to three beagle dogs and blood moxidectin concentrations were measured for 180 days.
[0212] In Example 3, the microparticles of the present invention were administered to a total of 10 beagle dogs so that the dose of moxidectin was 0.2 mg / kg, and the concentration of moxidectin in the blood was measured for 180 days.
[0213] The experimental results are shown in Tables 10 and 11 below and in FIG. [Table 10] [Table 11]
[0214] According to the above experimental results, the commercially available ProHeart SR-12 shows a large difference in blood concentration between beagle dogs, whereas Example 1 of the present invention shows that the blood moxidectin concentration of 10 beagle dogs was measured with a deviation of 0.2 to 2.39, which is not a large difference.
[0215] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also fall within the scope of the present invention. [Industrial Applicability]
[0216] The present invention relates to microparticles containing moxidectin and sustained-release injectable compositions containing the same.
Claims
1. Microparticles comprising moxidectin and a biodegradable polymer, The intrinsic viscosity of the biodegradable polymer is 0.1 dl / g to 1 dl / g; The average diameter of the microparticles is 60 to 110 μm. Microparticles containing moxidectin.
2. The microparticles are spherical; Moxidectin is uniformly contained within the microparticles.
2. A microparticle comprising the moxidectin of claim 1.
3. The coefficient of variation (CV) of the microparticles is 5% to 20%; 2. A microparticle comprising the moxidectin of claim 1.
4. The microparticles contain a biodegradable polymer and moxidectin in a weight ratio of 2:1 to 12:
1.
2. A microparticle comprising the moxidectin of claim 1.
5. The microparticles release moxidectin for a sustained period of at least three months.
2. A microparticle comprising the moxidectin of claim 1.
6. The biodegradable polymer is selected from the group consisting of polylactide (PLA), polylactide-co-glycolide (PLGA), polyphosphazenes, polyiminocarbonates, polyphosphoesters, polyanhydrides, polyorthoesters, polycaprolactones, polyhydroxyvalers, polyhydroxybutyrates, polyamino acids, and mixtures thereof; 2. A microparticle comprising the moxidectin of claim 1.
7. The microparticles have a molecular weight of 0.3 to 3 according to the following formula 1:
2. A microparticle comprising moxidectin according to claim 1 : [Formula 1] C max-peak n / C max―peak n+1 Where: Microparticles containing moxidectin were mixed with a suspension solution to prepare an injection, which was then administered to a beagle dog, and the blood concentration of moxidectin was measured. C max-peak n is the Cmax value of the nth order after administration of the injection; C max-peak n+1 is the n+1-th Cmax value due to the blood concentration of moxidectin increasing again after the n-th Cmax value.
8. 0.2 mg / kg of moxidectin was administered as the injection to a number of beagle dogs, and the concentration of moxidectin in the blood was measured. The standard deviation of the blood moxidectin concentration among beagle dogs administered the injection is 0.01 to 10. A microparticle comprising the moxidectin of claim 7.
9. A microparticle comprising the moxidectin of claim 1; and a suspension solution. A sustained release injectable composition comprising moxidectin.
Citation Information
Patent Citations
Sustained-release pharmaceutical composition composed of fine particles
JP2010529106A
Emulsion-based process for preparing fine particles, and workhead structure used in the process.
JP2013515059A
Sustained release formulation comprising octreotide and two or more polylactide-co-glycolide polymers
JP2015044823A
Microparticles containing gnrh produced by pgss
JP2016534040A
Microparticles containing moxidectin and methods for producing the same
JP2021509662A